The functional antagonist of sphingosine-1-phosphate, FTY720, impairs gut barrier function - Sikdar, Sohini; Mitra, Debmalya; Das, Oishika; Bhaumik, Moumita; Dutta, Shanta (Frontiers in Pharmacology, 2024)
Pharmacology as a brief report. On behalf of coauthors, I declare this work is original and has not been published elsewhere, nor is it currently under consideration for publication elsewhere.We have no conflicts of interest to disclose. FTY720 or Fingolimod is a drug commonly used in the treatment of Multiple Sclerosis. In this brief report we show that FTY720 treatment in mice can cause impairs barrier function by affecting the tight junction protein expression in gut and thereby leading to gut inflammation.We believe, this is an important observation as a vigilance on gut inflammation should be maintained in the patients receiving this drug for autoimmune disorders.